Surveillance of Escherichia coli clones and their antimicrobial resistance profiles in wastewater and drinking water treatment plants of Barcelona, Spain - Victoria Ballén; Enmanuel Cornielle; Anna Pinar-Méndez; Carles Vilaró; Belén Galofré; Sara Martí; Aida González-Diaz; Sergi Sanz; Aniol Vilamala; Sara M. Soto (PLoS ONE, 2026)
Antimicrobial resistance (AMR) is a major global health threat, and environmental reservoirs such as wastewater (WWTPs) and drinking water treatment plants (DWTPs) may facilitate its persistence and spread despite reducing bacterial loads. We investigated 152 antibiotic-resistant Escherichia coli strains collected across treatment stages from two WWTPs and one DWTP in Barcelona, Spain. Strains were characterized through antimicrobial susceptibility testing, whole-genome sequencing, multilocus sequence typing, biofilm assays, and screening of antimicrobial resistance genes (ARGs), virulence factors (VFGs), biocide and heavy-metal tolerance genes (HMTGs). Although E. coli bacterial loads decreased along treatment, AMR remained highly prevalent: 85.5% of strains were multidrug-resistant (MDR), 5.3% extensively drug-resistant, and 11.2% carbapenemase-producers. Strains harboring integrase genes were 2.4 to 11.8 times more likely to harbor ARGs for sulfonamide, aminoglycoside, phenicol, trimethoprim, mercury and quaternary-ammonium compounds. Strains carrying bla CTX-M genes were 3.0 to 20.3 times more likely to carry VFGs, while high-risk clones were 3.2 to 7.0 times more associated with VFGs. Some MDR and high-risk E. coli clones persisted in reclaimed water, and one MDR strain was detected at the DWTP inlet. These findings highlight environmental AMR reservoirs as a public health concern and support a One Health approach integrating antibiotic stewardship and environmental monitoring.